Efficiency Evaluation of European Countries in terms of COVID-19 - YURTSEVER, ÖZLEM (My University, 2021)
The COVID-19 Pandemic has effected millions of people all over the world. Therefore, the behaviour of countries is importantto minimise the losses. In this paper the performance of 27 European countries on spread and deaths caused by COVID-19pandemics is evaluated and compared by using input-oriented data envelopment analysis (DEA) method. The model isperformed in two steps. In the first step, the contagion control efficiency is analysed whereas in the second step the medicaltreatment efficiency is evaluated. Moreover, the countries are classified into the four zone by using the area chart. For thecountries in each zones, some recommendations are given.

COVID-19 pandemisi tüm dünyada milyonlarca insanı etkilemektedir. Bu nedenle, ülkelerin davranışları, kayıpları en aza_x000D_ indirmek için önemlidir. Bu araştırmada 27 Avrupa ülkesinin COVID-19 salgının neden olduğu yayılma ve ölümler üzerindeki_x000D_ performansı, girdi odaklı veri zarflama analizi (VZA) yöntemi kullanılarak değerlendirilmiş ve karşılaştırılmıştır. Buradak’_x000D_ model iki aşamada gerçekleştirilmiştir. İlk aşamada, bulaşma kontrolünün etkinliği analiz edilirken, ikinci aşamada tıbbi tedavi_x000D_ etkinliği değerlendirilmiştir. Ayrıca, ülkeler alan grafiği kullanılarak dört bölge de sınıflandırılmıştır. Her bölgedeki ülkeler_x000D_ için bazı öneriler verilmiştir
Avrupa Ülkelerinin COVID-19 Açısından Verimliliklerinin Değerlendirmesi